To the Interchange Instability Criterion in the Magnetosphere in the Presence of Velocity Shear. Issue 10 (16th October 2020) - Khazanov, George V.; Krivorutsky, Emanuel N.; Chen, Margaret W.; Lemon, Colby L.
Abstract: In this paper, we address the issue of interchange instability excitation criterion in the magnetospheric plasma in the presence of the velocity shear using a magnetohydrodynamic approach. We conducted our analysis for the arbitrary β plasma configuration using a WKB approximation for wavelengths, λ, much smaller than the characteristic plasma inhomogeneity scale, L, and found two branches of waves. These two wave branches can exist due to the plasma velocity shear and one branch can be unstable for arbitrary angles between the plasma entropy parameter and magnetic flux tube volume gradients. The implications of these results for magnetospheric physics as well as comparison of our results with corresponding analysis of other authors are discussed. Key Points: Criterion of interchange instability development in the magnetospheric plasma is derived The role of the velocity shear in interchange instability excitation is discussed The possible impact of the velocity shear on the plasma sheet interchange stability is considered